2011
DOI: 10.1152/ajpregu.00314.2011
|View full text |Cite
|
Sign up to set email alerts
|

“Liking” and “wanting” of sweet and oily food stimuli as affected by high-fat diet-induced obesity, weight loss, leptin, and genetic predisposition

Abstract: Cross-sectional studies in both humans and animals have demonstrated associations between obesity and altered reward functions at the behavioral and neural level, but it is unclear whether these alterations are cause or consequence of the obese state. Reward behaviors were quantified in male, outbred Sprague-Dawley (SD) and selected line obesity-prone (OP) and obesity-resistant (OR) rats after induction of obesity by high-fat diet feeding and after subsequent loss of excess body weight by chronic calorie restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
95
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 83 publications
14
95
0
3
Order By: Relevance
“…This observation is in concurrence with the report that CR causes reductions in body weight and normalization of blood glucose and hormone levels in obese animals as well as in nonhuman primates (35). Another study showed that CR reversed the alterations in taste-guided responsiveness that was induced by high-fat diet feeding in rats (28). The pair-feeding regimen imposed on the HC rats involved restriction of rodent chow for the HC/PF rats on a daily basis from the time of weaning, whereas CR in other animal models involved food restriction ranging from 20 to 40% during the period of investigation and in most studies was imposed on older animals.…”
Section: Discussionsupporting
confidence: 89%
“…This observation is in concurrence with the report that CR causes reductions in body weight and normalization of blood glucose and hormone levels in obese animals as well as in nonhuman primates (35). Another study showed that CR reversed the alterations in taste-guided responsiveness that was induced by high-fat diet feeding in rats (28). The pair-feeding regimen imposed on the HC rats involved restriction of rodent chow for the HC/PF rats on a daily basis from the time of weaning, whereas CR in other animal models involved food restriction ranging from 20 to 40% during the period of investigation and in most studies was imposed on older animals.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, it is tempting to speculate that GLP-1 increases the "fatty" taste sensitivity by participating in the dynamic regulation of lingual CD36 during the prandial period (121). Conversely, systemic leptin injection reduces a behavioral response to low corn oil concentrations, compared with saline injection, in rats subjected to brief-access licking tests (192). Finally, a regulatory loop linking LCFA, endocannabinoids, and preference for fat has also been recently identified in the rat (40).…”
Section: Iiib3) Did Not Occur In Glp-1rmentioning
confidence: 99%
“…by guest, on May 11, 2018 www.jlr.org Downloaded from measure taste-guided reward behavior [i.e., hedonic value and motivation ( 27 )]. Therefore, computer-controlled lickometers were used to measure the number of licks for 1 min and determine the attraction for 0.5% OLA or 0.5% LA solubilized in mineral oil.…”
Section: Gpr120-null Mice Detect and Prefer Lipid Solutionsmentioning
confidence: 99%